Peningkatan Keterampilan Menulis Teks Eksposisi Menggunakan Model Concept Sentence Siswa Kelas V SDN 26 Rimbo Kaluang Padang Barat - Hafifah, Nabila; Sukma, Elfia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the planning, implementation and improvement of narrative text writing skills using the Concept Sentence learning model in grade V of SD Negeri 26 Rimbo Kaluang West Padang. This type of research is Classroom Action Research (PTK). This research was carried out in 2 cycles with the stages of planning, implementation, observation and reflection. Data was collected using tests and interviews. The data was analyzed descriptively quantitatively with a percentage formula. The results of the study showed that the average value of teacher and student activities in cycle 1 of meetings 1 and 2 was 82.5 with a qualification of Good (B). Then in the second cycle, a score of 94.4 for teacher activities and 94.4 student activities with very good qualifications (A) was obtained. This shows the success rate of the implementation of writing learning in exposition texts using the Concept Sentence model in class V of SDN 26 Rimbo Kaluang, West Padang is included in the very good category because it has improved. In cycle I, the average value of Exposition text writing skills was 71.1 with a sufficient predicate (C), increasing in cycle II, which obtained an average score of Exposition text writing skills was 86.3 with a good predicate (B).